The structure, composition and preparation of injection-molded composite materials based on glass-filled polysulfone - A. B. Baranov; T. I. Andreeva; I. D. Simonov-Emelʼyanov; O. E. Peksimov (Тонкие химические технологии)
In the course of this study, compositions and designed structures for the polysulfone (PSF) and short glass fibers systems were calculated. Additionally, disperse-filled polymer composite materials (DFPCM) based on PSF-190 were classified in accordance with their respective structures, and the optimal amount of glass fiber (13.5–18.5 vol %) was determined. This article describes the production of DFPCM using PSF and a short glass fiber with a twin-screw extruder (Labtech Engineering Company LTD, model Scientific FIC 20-40). Furthermore, optimal mixing parameters for the creation of composites wherein the glass fiber length exceeds the critical length (lcr) were established. The critical length was calculated, and the curves for fiber size distribution of polysulfone composites were depicted, and a difference in fiber concentration between the dispenser and the extrusion head (up to ~10–15%) was found when the fiber content was at 18–25 vol %. For the first time, optimal parameters (which pertain to medium-filled dispersions) for the structure of DFPCM based on PSF and short glass fiber are able to be demonstrated.